Development of Professional Potential of University Teachers Based on HRM Practices - Khairulla , Bagila; Myrzabekov , Yerzhan (Pedagogy and Psychology, 2025)
The higher education system in the modern world faces the challenge of developing highly professional teaching staff capable of preparing competent HR specialists for the labor market. University teachers must demonstrate exceptional professionalism and continuously develop their capabilities to meet contemporary educational demands. The emphasis on developing professional potential of university teachers based on human resource management practices has become increasingly critical for educational quality and institutional effectiveness. Methodology and Methods. This study employs a comprehensive analysis of professional potential development frameworks and HRM practices in higher education. The research examines the structural components of professional potential, including professional competence, innovative readiness, and social, cultural, and moral potential. The methodology is grounded in the hypothesis that professional potential represents a manifestation of human potential within labor relations context. Results. The analysis reveals that professional potential serves as a fundamental condition for effective teaching activity and acts as a general indicator of professional competence and self-improvement. Professional competence emerges as a result of professional education, characterized by high-level professional self-awareness, holistic pedagogical vision, and systematic development of abilities for sociocultural self determination and creative self-realization. The findings demonstrate that professional competence represents an effective category encompassing knowledge management, skill development, personal experience integration, and consequent professional potential enhancement. Scientific Novelty. This research provides a comprehensive framework for understanding professional potential as an interconnected system of competencies specifically tailored to university teaching contexts. The study introduces innovative approaches to integrating HRM practices into academic professional development. Practical Significance. The findings offer practical guidelines for higher education institutions to systematically develop teacher professional potential, ultimately improving educational quality and preparing students for successful professional careers in HR and related fields.